2018
DOI: 10.3390/f9110668
|View full text |Cite
|
Sign up to set email alerts
|

Factors Explaining the Interest of Adult Offspring in Succeeding Their Parents as Forest Owners

Abstract: In the past, Swedish ownership of the forest estate was predominantly passed on by parents to their descendants. However, a general societal change has given successors a larger say in decisions on such matters. Their willingness to become forest owners has, therefore, become an important factor for who will own the forest in the future. To study what factors explain adult descendants’ interest in taking over as forest owners, this study determined how adult children, who expressed a willingness to take over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Additionally, having no successors might be detrimental, as Onda et al [115] found that older small-scale private forest owners in two study regions in Japan had very low motivation and unambitious future intentions for forest management if they had no successors. Two additional considerations are that the objectives of owning a forest might shift with a new generation taking over [120], and the transfer of ownership depends on the heirs' willingness to accept forest ownership [121][122][123].…”
Section: Higher Financial Compensation May Not Always Be Preferredmentioning
confidence: 99%
“…Additionally, having no successors might be detrimental, as Onda et al [115] found that older small-scale private forest owners in two study regions in Japan had very low motivation and unambitious future intentions for forest management if they had no successors. Two additional considerations are that the objectives of owning a forest might shift with a new generation taking over [120], and the transfer of ownership depends on the heirs' willingness to accept forest ownership [121][122][123].…”
Section: Higher Financial Compensation May Not Always Be Preferredmentioning
confidence: 99%